Taxonomic notes and redescriptions of some Japanese erythroneurine leafhoppers (Hemiptera, Cicadellidae, Typhlocybinae) - Ohara, Naomichi (Zootaxa, 2013)
In the Japanese typhlocybine fauna, three already known and three newly recorded species of the genera Anufrievia, Empoascanara, and Anzygina are redescribed and reported with brief notes on their taxonomy and biology: A. akazu (Matsumura), A. ciconia Dworakowska, E. bisignatella (Matsumura) comb. nov., new record, E. kotoshonis (Matsumura) new record, E. sonani (Matsumura) and A. honiloa (Kirkaldy) new record. Male specimens of A. akazu and E. bisignatella are described for the first time.